International Organizations and Lifelong Learning - Jakobi, A. author. aut Link
XVI, 227 p. 1 illus.
Keywords: In recent years lifelong learning has become one of the most prominent education policy goals. This book shows how international organizations have promoted this idea and disseminated the need for it to countries all over the world. As a consequence of their activity, lifelong learning has become a central element of modern education policy.